Noise Suppression Phenomenon in Fiber Raman Amplifier - Felinskyi Georgii; Dyriv Mykhailo (Measurement Science Review, 2015)
The problem of small bit error rate is actual in fiber Raman amplifiers. Our experimental data on the amplified spontaneous emission (ASE) with backward pumping as a base of optical noise evaluation are presented in this paper. Raman gain spectrum for useful Stokes low-powered signal is calculated and compared with obtained spectrum of non-coherent ASE noise. It is shown that output optical signal has better gain than the amplified spontaneous emission that leads to appreciable growth of output optical signal-to-noise ratio.